Pengkatalogan dan pengkelasan bahan; monograf, bahan bersiri dan bahan multimedia - Suja', Balqis (2010)
This is a two-hour presentation for support staff group to introduce them on the objectives and basics of cataloguing. Participants were made exposed to source of the cataloguing code, i.e. AACR2 and format for recording bibliographic information using MARC21 and its end product in the form of catalogue and OPAC display. The lecture ended with a brief group exercise on how to record details from chief source of information into MARC input sheet.